Pengelolaan Kawasan Wisata Suku Anak Dalam Berbasis Kearifan Lokal - Wazan, Syafik; Astuti, Retno Sunu; Kismartini, Kismartini; Afrizal, Teuku (PERSPEKTIF, 2020)
The purpose of this study is to analyze the Management of the Children in the Tourism Area of the Children in the Tribe and to find out the obstacles in the management of the Children in the Tourism Area in the Bukit Duabelas National Park, the Sorolangun Regency, the Jambi Regency. The theory uses the opinion of Cox (1985) in Pitana (2009) on tourism management must pay attention to principles such as Development, Preservation, Development, Service and Regulation / legal certainty. The research method uses a descriptive qualitative approach. This research was carried out in the settlement of the Children of the Tribe in the Sorolangun Regency, Jambi Province. Data collection uses observation, interviews (FGD), and Documentation / Similar Research. The results of research on the management of the Suku Anak Dalam tourism area (SAD) have provided comfort to visitors without disturbing or disturbing the ecosystem or the authenticity of the tourist attractions. With the existence of this educational tourism management will increase the original income of the region in the field of tourism. This must be maintained so that later other tourism objects will emerge. It's just that there is a need for a regional regulation for the development of special tourism areas for children in the tribe so that treatment can be felt directly to the community.